Novel Thiazole Derivatives of Medicinal Potential: Synthesis and Modeling - Nour E. A. Abdel-Sattar; Abeer M. El-Naggar; M. S. A. Abdel-Mottaleb (Journal of Chemistry)
This paper reports on the synthesis of new thiazole derivatives that could be profitably exploited in medical treatment of tumors. Molecular electronic structures have been modeled within density function theory (DFT) framework. Reactivity indices obtained from the frontier orbital energies as well as electrostatic potential energy maps are discussed and correlated with the molecular structure. X-ray crystallographic data of one of the new compounds is measured and used to support and verify the theoretical results.